2008
DOI: 10.1074/jbc.m800593200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Proline Focuses Movement of the Floppy Loop of Arylalkylamine N-Acetyltransferase (EC 2.3.1.87)

Abstract: Arylalkylamine N-acetyltransferase (AANAT) catalyzes the N-acetylation of serotonin, the penultimate step in the synthesis of melatonin. Pineal AANAT activity increases at night in all vertebrates, resulting in increased melatonin production. This increases circulating levels of melatonin, thereby providing a hormonal signal of darkness. Kinetic and structural analysis of AANAT has determined that one element is floppy. This element, termed Loop 1, is one of three loops that comprise the arylalkylamine binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…These results should be interpreted with care; however, differences in the ionic interaction between Glu191 and Arg104 are the sort of changes conferred by the Val160Ala mutation that could contribute to rendering saAANAT2_IA and mutant VA more thermal tolerant. It has been shown that a single or a few amino-acid substitutions can affect the impact of temperature on enzyme kinetics when these appear in regions likely to influence the conformational mobility of regions involved in catalytic conformational changes (Holland et al, 1997;Pavlicek et al, 2008). However, the differences in thermal tolerance existing between saAANAT2_IA and the VA mutant on the one hand, and saAANAT2_VV and omAANAT2_IV on the other hand, suggest that the 114 position also plays a role.…”
Section: The Journal Of Experimental Biology 216 (10)mentioning
confidence: 82%
“…These results should be interpreted with care; however, differences in the ionic interaction between Glu191 and Arg104 are the sort of changes conferred by the Val160Ala mutation that could contribute to rendering saAANAT2_IA and mutant VA more thermal tolerant. It has been shown that a single or a few amino-acid substitutions can affect the impact of temperature on enzyme kinetics when these appear in regions likely to influence the conformational mobility of regions involved in catalytic conformational changes (Holland et al, 1997;Pavlicek et al, 2008). However, the differences in thermal tolerance existing between saAANAT2_IA and the VA mutant on the one hand, and saAANAT2_VV and omAANAT2_IV on the other hand, suggest that the 114 position also plays a role.…”
Section: The Journal Of Experimental Biology 216 (10)mentioning
confidence: 82%
“…Activity was 5-to 10-fold higher in the retina than Major structural differences between NV-and VT-AANAT include the addition of PKA/14-3-3 binding sites flanking the core of the enzyme, which mediate regulation, the addition of histidines to facilitate catalysis by promoting removal of protons generated during the transfer of the acetyl group, and the addition of a short peptide sequence (Cys-Pro-Leu), which creates a floppy loop that facilitates arylalkylamine binding and product release in the active site. The highly conserved lysine found in the N-terminal flanking regions of VT-AANAT is thought to facilitate regulation of proteasomal proteolysis by serving as a ubiquitination site (10,13,14,25,26,28,29). Modified from ref.…”
Section: Resultsmentioning
confidence: 99%
“…The encoded proteins (206 and 207 aa) exhibited the two defining features of the GCN5 N-acetyltransferase superfamily, motifs A and B (SI Appendix, Fig. S1) (9,(22)(23)(24)(25)(26)(27)(28)(29). In addition, the sequences exhibited defining characteristics of the VT-AANATs of bony vertebrates, including motifs C and D, PKA sites nested in 14-3-3 binding domains, a Cys-ProLeu peptide sequence in a floppy loop within the binding region, and closely positioned histidine residues in the active site.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the side chain of proline can wrap around to form a covalent interaction with the backbone, restricting its flexibility and limiting the conformation of neighboring residues (40). Therefore, proline has a unique role in determining local conformation and movement freedom in the folded protein, functioning as a molecular switch in the regulation of a number of cellular processes (39,41,42). In the metal sensors, the restricted set of conformations adopted by Pro at position 113 or 118 may differentially affect chain dynamics and the range of conformations the metal-binding loop can assume.…”
Section: Discussionmentioning
confidence: 99%